2000
DOI: 10.1053/jhep.2000.16183
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Reactive Oxygen Species and Mitochondrial Permeability Transition in Microcystin-Induced Rapid Apoptosis in Rat Hepatocytes

Abstract: Microcystin-LR (M-LR) is a specific hepatotoxin.At present, the exact toxic mechanism of its action remains unclear though apoptosis is believed to be involved. This study was designed to investigate the role of reactive oxygen species (ROS) and mitochondrial permeability transition Cyanobacteria (blue-green algae) are a group of photosynthetic organisms found in both freshwater and marine environments. Some of the genera are capable of producing various toxins, causing serious public health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
140
0
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 227 publications
(157 citation statements)
references
References 41 publications
10
140
0
5
Order By: Relevance
“…14 It has also recently been postulated that CaMKII is activated late in the process of microcystin-induced apoptosis through increase of intracellular Ca 2 þ secondary to severe mitochondrial damage. 15,16 This would imply that CaMKII only has a role late in the downstream apoptosis signaling modulating the phenotype of PP-inhibitor-induced death.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has also recently been postulated that CaMKII is activated late in the process of microcystin-induced apoptosis through increase of intracellular Ca 2 þ secondary to severe mitochondrial damage. 15,16 This would imply that CaMKII only has a role late in the downstream apoptosis signaling modulating the phenotype of PP-inhibitor-induced death.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of mitochondria, including an increase of reactive oxygen species followed by a loss of mitochondrial membrane potential was observed (Ding et al, 2000). Moreover, mitochondria have been found to be one of the major targets in the MC-LR induced apoptotic process, and the onset of mitochondrial permeability transition (MPT) precedes the characteristic signs of apoptosis (Ding et al, 2000). Ding et al (2001) showed that MC-LR caused an early surge of mitochondrial Ca 2+ prior to the onset of MPT and cell death in MC-LR treated rat hepatocytes.…”
Section: Introductionmentioning
confidence: 98%
“…inhibition of serine/threonine phosphatases-1 and -2A (Mackintosh et al, 1990) and/or to the increased formation of reactive oxygen species (Ding et al, 2000). Cytoskeletal changes and apoptosis induced by microcystins were found in experiments on cultured rat hepatocytes and kidney cells (Eriksson et al, 1989;Falconer and Yeung, 1992;Wickstrom et al, 1995).…”
mentioning
confidence: 94%
See 2 more Smart Citations